PERANCANGAN PERANCANGAN SISTEM INFORMASI SEWA SEPEDA BERBASIS WEBSITE: STUDI KASUS PADA JOGJABIKE - Rifqi Tri Mabruri; Wibawa Wibawa; Ari Kusuma Wardana; Arifah Indah Setyorini (Jurnal Dinamika Informatika, 2023)
JogjaBike is an agency in Yogyakarta, where JogjaBike provides tourist bicycle rental services. There are types of MTB bikes, city bikes, folding bikes, and others. However, there have been obstacles in the business process so far, namely the absence of multi-platform digital information about unit availability, types of bicycles, order schedules, bookkeeping, electronic payments, and report generation. Because it still uses a manual process, to complete the administration of orders, the calculation of payment costs is still done manually. Reporting to the admin still uses written reports in the administration section. Based on these problems, JogjaBike requires a website-based tourist bicycle rental information system for the efficient time needed to find the availability of bicycle units, speed up payment calculations made online, and provide reports to the JogjaBike admin. The result of this research is a tourist bicycle rental transaction information system that can display the availability of bicycle units, and choice of bicycle types, speed up registration, speed up the calculation of detailed rental fees, reduce the possibility of errors in the calculation process, and generate reports to the admin.